Approaching a dynamic view on the availability of mineral resources: What we may learn from the case of phosphorus? - Scholz, Roland W.; Wellmer, Friedrich-Wilhelm (Global environmental change, 2013)
► The Hubbert curve is an inadequate model for predicting global phosphorus reserves. ► Physical scarcity and economic scarcity have to be distinguished. ► There is geological evidence for economically mineable phosphorus for centuries. ► There is incomplete knowledge about total phosphorus resources/reserves which are dynamic figures. ► The complexity of sustainable P management necessitates a transdisciplinary approach. This paper elaborates in what way a dynamic perspective on reserves, resources and geopotential is necessary to provide robust estimates on resource availability. We introduce concepts of essentiality, criticality and economic scarcity and discuss for the case of phosphorus (P) how they are defined and may be measured. The case of P is considered in detail as P an essential element for global food security with a highly dissipative use and is geographically unevenly distributed across the globe. We distinguish and relate the complementarity between physical and economic scarcity and discuss limits and potential of static indicators such as static lifetime, Hubbert curve applications, and the Herfindahl–Hirschman-Index of P for predicting future availability of these resources. We reveal that these static indicators are – in general – not valid approaches to predict physical scarcity of resources. Geological data show that though the P reserves have not been systematically and completely assessed on a global scale, the static lifetime of P is high. When acknowledging socio-economic and technological dynamics, and available geological facts, statements predicting physical scarcity or a peak in P production within a few decades are unlikely to be accurate or valid. We elaborate that some simplified indicators such as static lifetime or the Hubbert curve based prediction of peaks may serve as screening indicators preceding early warning research, which may induce increased mining activities, technology innovation or other actions. However, in general, these simplified indicators are not valid approaches to predict physical scarcity of resources. Although one day there may be a supply-driven P production peak, demand-driven production plateaus and multiple peaks are probable in the near future. Given its geopotential, essentiality, and the learning curve of efficient fertilizer use, P is subject to demand-driven market dynamics. Thus, a symmetric decline and unavoidable shortage of P in the next decades are unlikely. This insight does not refute the need to close the anthropogenic P loop. Activities associated with P production and consumption use has a significant pollution potential in part because of the dissipative nature. The paper reveals the necessity to mitigate risks (such as economic scarcity, especially for poor farmers) of both short-term price peaks and longer lasting step-changes in price, e.g. due to knowledge gaps of technological adaptation in energy and water management or other reasons of insufficient supply-demand dynamics management. The complexity of this task necessitates a transdisciplinary approach.